Measuring achievement in grammar and Composition I in the Philippine College of Commerce High School - Arbis, Leticia Reyes 1931- (s.n.], 1964)
This study aims to present an objective test designed to measure achievement in English grammar and Composition I in the Philippine College of Commerce High School, and to describe how such a test may be constructed.